Il Violino, ossia analisi del suo meccanismo: III vv., Furchheim-Hoepli, Napoli 1883/1884/1888. (Ex Chordis, 2024)
Eusebio Dworzak von Walden (1850-1905), born in Braila, Romania, the son of the Austrian consul in Patras, first studied in Delphi and then graduated from the Leipzig Conservatory under Ferdinand David. After a period of teaching at the Leipzig Conservatory, he moved to Naples in the 1980s, becoming head of the Violin and Viola Department at the S. Pietro a Maiella Conservatory and one of its most important teachers. A Neapolitan schoolmaster, he boasts among his pupils Gaetano Fusella (1876-1973), Alfredo D'Ambrosio (1871-1915), Luigi D'Ambrosio (1885-1972), some of the most important names of the Neapolitan Violin School, as recalled in Pasquali-Principe's Manuale di cultura e didattica violinistica (1926): ‘from his school came pupils who also emerged for their violinistic and didactic qualities’.